Progressive collapse of structures - Starossek, Uwe (ICE Publishing, 2018)
Sets out a practical, systematic framework to give engineers the tools they need to anticipate the risk of progressive collapse of structures and apply this knowledge to design and assessment procedures.
This edition previously issued in print in 2017. Digital resource published 2018.
Keywords: Structural failures.; Structural failures -- Prevention.; elektronické knihy; electronic books